THE EFFECT OF LIQUIDITY ANALYSIS ON THE PERFORMANCE OF BANKS (World Economics and Finance Bulletin, 2024)
The impact of liquidity ratios on commercial banks' financial performance is the main topic of the study. Eleven banks, or around 46% of all the commercial banks listed on the Iraqi Stock Exchange, were employed in the research. The time frame that was used was 2010–2023. The focus was on evaluating the link between the legal liquidity ratio and return on equity (ROE), return on assets (ROA), and net interest margin (NIM) using the available software, EViews V 10. Since the fixed effect model is the most suitable for evaluating the link between independent and dependent variables, it was used to analyse the data. The findings show that the legal liquidity ratio and net interest margin (NIM) have a statistically significant negative connection; that is, a higher liquidity ratio will result in a lower profit margin. Additionally, it has been shown that the employment ratio has a negative, non-significant influence that could not always improve the profit margin. It was determined that financial liquidity and employment ratios directly impact banks' financial performance; hence, effective management of these ratios contributes to increased financial efficiency. pertains to this model; as a result, the research suggests that management enhance its liquidity management procedures and policies in order to attain optimum financial performance by preventing negative effects on return brought on by insufficient liquidity
Keywords: Following Liquidity Analysis; Bank Performance; Statutory Liquidity Ratio